Variation characteristics of stress distribution in the subchondral bone of the knee joint of judo athletes with long-term stress changes - Li, Zhiqiang; Xu, Guanghua; Wang, Chengjun; Wang, Qiuyuan; Liu, Caiping; Guo, Tingting; Wu, Lijun; Cao, Diankang (Frontiers in Endocrinology, 2023)
Objective To investigate the distribution of bone density in the subchondral bone tissue of the knee joint due to the mechanical stress load generated by judo, the bone tissue volume of different densities and the bone remodeling characteristics of the subchondral bone of the knee joint. Methods CT imaging data of the knee joint were collected from 15 healthy individuals as controls and 15 elite judo athletes. Firstly, they were processed by the CTOAM technique, and secondly, the distribution pattern of high-density areas of the knee joint was localized using nine anatomical regions. In addition, three tomographic images were selected in the sagittal, coronal, and axial 2D image windows to observe the distribution of different densities of bone tissue. Finally, the percentage of bone tissue volume (%BTV) and bone remodeling trend of bone tissues with different densities were determined. Results In this study, high-density areas were found in the 4th, 5th, and 6th regions of the articular surface of the distal femur and the 1st, 2nd, 3rd, 4th, 5th, 6th, 7th and 8th regions of the tibial plateau in judo athletes; the distribution of high-density areas on the articular surface of the distal femur in control subjects was similar with judo athletes, and high-density areas were mainly found in the 4th and 5th regions of the tibial plateau. The %BTV of low (401-500HU in the distal femur; 301-400 HU and 401-500HU in the tibial plateau), moderate, and high bone density was higher in judo athletes than in controls in the subchondral bone of the distal femur and tibial plateau (P< 0.05). Conclusion The history of compressive stresses, struck stresses, soft tissue tension and pull, self-gravity and intra-articular stress loading generated by the lower limb exercise technique of judo leads to specific forms of stress distribution and bone tissue remodeling in the subchondral bone tissue within the distal femur and tibia plateau.